“TRUTH IS IMMORTAL”: BALTHASAR HUBMAIER’S ENCOUNTER WITH THE BIBLE - Brasil de Souza, Guilherme (Práxis Teológica, 2024)
The following article argues that Anabaptist reformer Balthasar Hubmaier’s view of the Bible as an immortal truth – freely accessible to all who in response to God’s grace accepted freely its saving message – entailed an ecclesiology that stressed less the power of the church in controlling Christ’s presence and more the role of the individual’s relationship with God and with the body of believers. In attempting to make this argument I trace the development of Hubmaier’s thought from his early scholastic education, followed by his embrace of the faith of the reformers and finally to a Christocentric and Bible centric Anabaptist theological understanding of the church. The ultimate implications of this would be the expansion of the notion of Christian freedom and the reduction of the powers of the church.